2010
DOI: 10.4269/ajtmh.2010.10-0346
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Surveillance of Childhood Bacterial Meningitis in Senegal and the Introduction of Haemophilus influenzae Type b Conjugate Vaccine

Abstract: Abstract. Bacterial meningitis is an important cause of morbidity and mortality in children living in low-resource settings. Pediatric bacterial meningitis cases < 5 years of age were identified through a regional hospital surveillance system for 3 years after introduction of routine immunization with Haemophilus influenzae type b (Hib) conjugate vaccine in Senegal in July 2005. Cases from the national pediatric hospital were also tracked from 2002 to 2008. The regional surveillance system recorded 1,711 suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
1
9
0
1
Order By: Relevance
“…In our study the prevalence of confirmed and probable meningitis were 3.3% and 2.1% respectively. Our result is similar to other surveillance (based on cultures) of meningitis in other parts of Africa [ 33 , 34 ]. The prevalence however appears low compared to some reports from the northern part of Ghana.…”
Section: Discussionsupporting
confidence: 92%
“…In our study the prevalence of confirmed and probable meningitis were 3.3% and 2.1% respectively. Our result is similar to other surveillance (based on cultures) of meningitis in other parts of Africa [ 33 , 34 ]. The prevalence however appears low compared to some reports from the northern part of Ghana.…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, two main changes have been observed in the epidemiology of acute bacterial meningitis in children [ 25 ]. The first change was that the prevalence of Streptococcus pneumoniae , Haemophilus influenzae type b and Neisseria meningitides significantly decreased in some developed countries due to the administration of vaccines [ 26 , 27 ]. Similarly, the incidence of acute bacterial meningitis caused by with Streptococcus pneumoniae , Haemophilus influenzae type b and Neisseria meningitides also decreased in Yunnan province, China, where vaccinations were partially performed against these bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 29 S. pneumoniae meningitis tested with 28 different antisera, 16 different serotypes were identified, and serotypes 1 (6/29, 20.7%; 95% CI, 5-36%), was the most prevalent followed by 23 F (4/29, 13.8%), and 6B (3/29, 10.3%) (Figure 3 ). Serotype data have been obtained in 3 previous studies on meningitis in Senegal [ 19 ]-[ 21 ]. In the 70s the most frequent serotypes were 5, 6, 23 and 12, although serotype 1 was also detected (4-8%).…”
Section: Discussionmentioning
confidence: 99%